TRANSAKSI DERIVATIV VALUTA ASING DALAM TINJAUAN HUKUM PERJANJIAN DI INDONESIA - , Edi Wahananto, SH; , Sularto, S.H. C.N. M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Derivative transaction is developing vastly in money market and especially in foreign currency purchasing market. That condition happens generally because of the fluctuation of currency values. This research is mainly trying to figure out some explanations on derivative transaction specifically from Indonesian contract law perspective and is also trying to find out about the arrangement of this instrument according to Indonesian banking law. The research model used in this thesis is a normative-analytical model. The process starts with analyzing a bunch of laws or regulations related to the main proablems of this research, namely, derivative transaction and contract law. This phase is aimed to find some explanations whether a derivative transaction meets the conditions of contractual validity as mentioned in Indonesian Civil Code (BW) and also to figure out about the derivative transaction arrangement in Indonesian banking law. From the perspective of contract law, derivative transaction will be considered to be valid when it has complied with the contractual conditions based on article 1320 BW, which consists of meeting of minds, legal capacities among the contracting parties, certain matter, and rightful reason or permitted by law. In addition, derivative transaction is not similar with a speculative agreement. Derivative transaction is absolutely a legal banking product, because there is a complete set of regulations for such product in Indonesian banking law system.